The Effect Of Direct Reading Strategy Instruction On Students’ Reading Comprehension, Metacognitive Strategy Awareness, And Reading Attitudes Among Eleventh Grade Students In Yemen - Al-Tamimi, Nasser Omer Mubarak (2007)
The purpose of this study was to investigate whether direct reading strategy instruction (DRSI) would be effective in enhancing reading comprehension, metacognitive awareness of reading strategies and attitudes toward reading among Yemeni secondary school students who study English as a foreign language.